A multi-objective robust scenario-based stochastic chance constrained programming model for sustainable closed-loop agri-food supply chain - Rahbari, Misagh; Khamseh, Alireza Arshadi; Mohammadi, Mohammad (Computers & chemical engineering, 2025)
•Developing a sustainable closed-loop supply chain for canned food in a real case.•Presenting the RSSCCP approach to find the best practical decisions.•Utilizing carbon cap and trade mechanism to control environmental pollution.•Considering customer satisfaction and job opportunities to increase social impact. The agri-food supply chain management plays a crucial role in ensuring the interests of supply chain components and food security in society. Additionally, due to the nature of agri-food products, sustainability dimensions have always been of concern to organizations engaged in this field. The importance of the timely and quality provision of agri-food products has doubled after the global crisis. Therefore, this study focuses on optimizing and analyzing the sustainable multi-objective closed-loop supply chain network for agri-food products, with a case study on the canned food under uncertainty. Strategic and operational decisions and other features are considered to achieve more accurate results. To address the various dimensions of sustainability, the problem is considered as a four-objective one, aiming to maximize the use of available production throughput for factories, maximize job opportunities created, minimize supply chain costs, and ultimately minimize unmet demands. The carbon cap and trade mechanism is used to control greenhouse gas emissions in the supply chain network. A robust scenario-based stochastic chance constrained programming approach is employed to deal with the uncertainty, and also validation is performed using various criteria. Moreover, an augmented ε-constraint optimization approach is used to solve the multi-objective problem and achieve Pareto optimal solutions. Finally, sensitivity analysis is employed to prepare for potential changes in some problem parameters. [Display omitted]